AB1338-HPR GLOBAL PATIENT PERSPECTIVE ON TOP CHALLENGES IN LUPUS CARE AND RESEARCH PARTICIPATION. (2nd June 2020) - Tse, K.; Peña, Y.; Arntsen, K.; Bae, S. C.; Bloch, L.; Bruce, I. N.; Costenbader, K.; Dickerson, B.; Dörner, T.; Getz, K.; Kao, A.; Manzi, S.; et al.
Abstract : Background: The Addressing Lupus Pillars for Health Advancement (ALPHA) Project is a global consensus initiative to identify, prioritize and address top barriers in lupus drug development, clinical care and access to care. The Lupus Foundation of America convenes ALPHA with Tufts Center for the Study of Drug Development and a Global Advisory Committee of lupus experts representing clinician-scientists, industry and patients. Objectives: Collect global patient input to determine alignment with the lupus clinician-scientist community on prior published consensus of top lupus barriers. Methods: A 23-question online Qualtrics survey was developed to identify challenges across lupus diagnosis, clinical care and research participation. The survey, available in English, Spanish, Korean and simplified Chinese, was fielded in November 2019 to people with lupus and caregivers of children <18 with lupus. SPSS 26 and SAS 9.4 were used for descriptive statistics and sub-analysis. Results: Analysis included only consented responses with ≥ 68% survey completion (n=3, 447) received across 83 countries. 95% were female with a mean age of 45. Respondents reported being White (57%), Black or of African descent (14%), Hispanic or Latino (18%) and Asian (10%). 65% resided in the US while 35% resided in countries outside of the US. 97% were people with lupus while 3% were caregivers to children <18 with lupus. Highest ranked challenges were similar globally and across children and adults: medication side effects, lack of treatment options and high out-of-pocket costs. Managing side effects ranked significantly higher (p<.05) outside of the US (48%) compared to US (40%). 50% of caregivers reported managing side effects as the top challenge for children compared to 43% of adults (p<.05). Research participation was low (24%) and lower among children (16%). The top reason for not participating in a clinical trial was not being asked by their doctor. Conclusion: This global survey revealed that medication side effects and lack of effective treatments are top challenges for people with lupus, including children. Most respondents were never asked by their doctors to participate in a clinical trial, which may explain difficulties in trial recruitment. These barriers are consistent with prior published barriers identified by the clinician-scientist community. Acknowledgments: ALPHA sponsors: EMD Serono, GSK, Aurinia, Mallinckrodt Disclosure of Interests: Karin Tse: None declared, Yaritza Peña: None declared, Kathleen Arntsen: None declared, Sang-Cheol Bae: None declared, Lauren Bloch Consultant of: Faegre Drinker Consulting is a division of Faegre Drinker Biddle & Reath, a law and consulting firm that represents patient advocacy organizations and sponsors developing drugs, Ian N. Bruce Grant/research support from: Genzyme Sanofi, GSK, and UCB, Consultant of: Eli Lilly, AstraZeneca, UCB, Iltoo, and Merck Serono, Speakers bureau: UCB, Karen Costenbader Grant/research support from: Merck, Consultant of: Astra-Zeneca, Bradley Dickerson Employee of: Aurinia, Thomas Dörner Grant/research support from: Janssen, Novartis, Roche, UCB, Consultant of: Abbvie, Celgene, Eli Lilly, Roche, Janssen, EMD, Speakers bureau: Eli Lilly, Roche, Samsung, Janssen, Kenneth Getz: None declared, Amy Kao Employee of: EMD Serono, Susan Manzi: None declared, Eric F. Morand Grant/research support from: AstraZeneca, Consultant of: AstraZeneca, Speakers bureau: AstraZeneca, Sandra Raymond: None declared, Brad H Rovin Grant/research support from: GSK, Consultant of: GSK, Laura Schanberg Grant/research support from: Sobi, BMS, Consultant of: Aurinia, UCB, Sanofi, Victoria Werth Grant/research support from: Biogen, Celgene, Gilead, Janssen, Viela, Consultant of: Biogen, Gilead, Janssen, Abbvie, GSK, Resolve, AstraZeneca, Amgen, Eli Lilly, EMD Serono, BMS, Viela, Kyowa Kirin, Joan Von Feldt Shareholder of: GSK, Employee of: GSK, David Zook Consultant of: Faegre Drinker Consulting is a division of Faegre Drinker Biddle & Reath, a law and consulting firm that represents patient advocacy organizations and sponsors developing drugs, Leslie Hanrahan: None declared